THE ACUTE EFFECT OF MENARCA IN PERCENTAGE OF FAT (Fiep Bulletin - online, 2014)
This article addresses an issue that has been worsening in recent years, young obesity. The knowledge of the percentage of body fat, satisfaction with body weight, are essential information for the educational and care with the health of school for pre - puberty and puberty adolescents. This study aims to present the percentage of fat in adolescence and their profiles in the pre-puberty and puberty bounded by the age of menarche, in the school of Cabo Frio, Rio de Janeiro. It is characterized as a descriptive study, the sample comprised of 144 schools of gender female, belonging to the municipality of Cabo Frio. To observe the effect of acute menarche on the percentage of fat was perceived that the percentage of fat has not produced significant differences between groups having demonstrated a homogeneous distribution of the samples which may indicate a uniformity also in the energy balance refers to the conclusion that habits food and physical maintain the same balance before and after menarche and the percentage of fat.
Keywords: Percent of fat; puberty; menarche